Detection of Theileria ovis in naturally infected sheep by nested PCR - Altay, K; Dumanli, N; Holman, PJ; Aktas, M (Elsevier, 2005)
A nested polymerase chain reaction (PCR) for the detection of Theileria ovis in sheep using oligonucleotide primers designed from the small subunit ribosomal RNA (SSU rRNA) gene sequence of T ovis from sheep in eastern Turkey is described. A 398bp DNA fragment was specifically amplified from blood samples from sheep, naturally infected with T ovis. No PCR products resulted from T. lestoquardi, T. annulata, T. parva, T. buffeli and Babesia spp. DNA using these specific primers. The sensitivity of the nested PCR for T ovis, which was assessed showed that one infected cell in 10(7) sheep erythrocytes, equivalent to a blood parasitemia of 0.00001%, could be detected. This is more sensitive than examining 200 fields under light microscopy. In addition, of the 124 field samples obtained from sheep in eastern Turkey tested, 19.35% (24/124) were positive for the presence of Theileria spp. by microscopic examination compared to 54.03% (67/124) positive for T ovis by nested PCR. The primer pairs described in this study will be useful for epidemiological studies on ovine theileriosis and for discrimination between T. lestoquardi and T ovis infections in sheep. (C) 2004 Published by Elsevier B.V.
Keywords: Theileria ovis; sheep; protozoa; nested PM microscopy; specific primers